Answer:
y = 3f(-1/5x + 1/5)
The function is
- vertical stretched by a factor of 3
- reflected across y-axis
- horizontal stretched by a factor of 5
- horizontal translated to the left 1/5 units
Explanation:
Starting with: y = f(x)
Replacing x with -1/5x: y = f(-1/5x)
Replacing x with x - 1: y = f(-1/5(x - 1)) = f(-1/5x + 1/5)
Replacing y with 1/3y: 1/3y = f(-1/5x + 1/5) or y = 3f(-1/5x + 1/5)
The transformation:
- kf(x) vertically stretches the function by a factor of k (here k is 3)
- f(-x) reflects the function across y-axis
- f(bx) horizontally stretches the function by a factor of 1/b (here b is 1/5)
- f(x + c) horizontally translates the function left c units (here c is 1/5 units)